Online Games and Their Effects on Student Learning Interest: A Correlation Study on Physical Education Subject in Merauke, South Papua - Yonatan Tambing Bontong; Martha Betaubun; Jori Lahinda; Kristian Paruty Lewier (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to analyze the influence of online games on the interest in learning Physical Education and Health (Penjas) in students. Online gaming has become one of the popular forms of entertainment among teenagers and young people. However, attention to its impact on academic learning interest, especially in the fields of Physical Education and Health, is still relatively limited. This study used a quantitative approach with correlation and regression analysis. The population and sample of the study were students of SMK Negeri 2 Tourism Merauke with a total sample from class XI of 25 students. Data was collected through questionnaires that focused on two main aspects: the frequency of playing online games and the students' learning interests. The results showed that there was a negative correlation between the frequency of playing online games and the students' learning interest. Factors contributing to the decline in interest in learning in students who frequently play online games include the use of unbalanced time between gaming and learning activities, as well as the psychological impact that may arise from addictive games. This research provides new insights into how online games can affect students' learning interests. The results of this study have important implications for educators and parents to understand the potential impact of playing online games on students' learning interests. Educators should consider creative ways to increase students' interest in PE learning, such as integrating interesting media or methods in learning or creating awareness about the importance of balancing gaming and learning activities in a balanced manner.